2004
DOI: 10.1300/j030v13n01_02
|View full text |Cite
|
Sign up to set email alerts
|

Electron Beam Irradiation for ReducingListeria monocytogenesContamination on Cold-Smoked Salmon

Abstract: Electron beam (e-beam) irradiation to reduce spoilage bacteria and Listeria monocytogenes on cold-smoked salmon was studied. Salmon fillets were inoculated with L. monocytogenes (4.4 ϫ 10 3 CFU/g) and exposed to e-beam radiation at doses of 1, 2, and 4 kGy. The e-beam irradiated samples were stored at 5°C and tested for psychrotrophs, mesophiles, and L. monocytogenes on days 1, 8 and 28. Total bacterial populations on cold-smoked salmon were reduced by e-beam processing but increased during storage. L. monocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
3
16
0
Order By: Relevance
“…A treatment with 2·0 kGy X‐ray significantly reduced the initial populations of psychrotrophic bacteria on smoked catfish to below the detectable limit (1·0 log CFU g −1 ). These findings are in agreement with those obtained by Su et al. (2004) who found that mesophilic count, on smoked salmon, was reduced to nondetectable levels after treatment with 1·0–4·0 kGy electron beam irradiation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A treatment with 2·0 kGy X‐ray significantly reduced the initial populations of psychrotrophic bacteria on smoked catfish to below the detectable limit (1·0 log CFU g −1 ). These findings are in agreement with those obtained by Su et al. (2004) who found that mesophilic count, on smoked salmon, was reduced to nondetectable levels after treatment with 1·0–4·0 kGy electron beam irradiation.…”
Section: Discussionsupporting
confidence: 93%
“…Taking this limit into account, the shelf life of smoked catfish was prolonged from 15 days for the controls to 35 days for the samples treated with 2·0 kGy X‐ray at 22°C. These results are also in the same trend as those obtained by Su et al. (2004) who reported that the total plate count of smoked salmon samples treated with 4 kGy remained at a low level of 3·75 log CFU g −1 after 28 days of storage at 5°C.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Listeria monocytogenes inactivation kinetics has been investigated in cold smoked salmon (Medina et al, 2009;Su et al, 2004), ready-toeat, vacuum-packaged smoked mullet (Robertson et al, 2006) and trout . Most studies obtain D 10 values for pathogens or test different processing conditions.…”
Section: New Efficacy Data Available In Scientific Literaturementioning
confidence: 99%
“…Panelists indicated that there were no differences among treated and untreated samples. Su et al (2004) studied electron beam irradiation to reduce spoilage bacteria and Listeria monocytogenes on cold-smoked salmon. Salmon fillets were inoculated with L. monocytogenes (4.4 * 10 3 CFU/g) and exposed to e-beam radiation at doses of 1, 2, and 4 kGy.…”
Section: Fishmentioning
confidence: 99%